Widening the arc of indigenous communication: Examining potential for use of ICT in strengthening social and behavior change communication efforts with marginalized communities in India. Issue 4 (30th May 2018) - Malhotra, Alka; Sharma, Rachana; Srinivasan, Raghavan; Mathew, Nirmala
Abstract: Marginalized communities in India have their own systems of governance, culture, and communication. They remain socially and physically distanced from mainstream methods of communication. At the same time, India is witnessing a digital revolution, represented by a phenomenal growth in mobile and internet penetration. To date, however, scholarly discourse on use of ICT among marginalized communities in India has, for the most part, been limited. Four related field studies initiated by UNICEF revealed that melding indigenous (local) and mainstream communication channels can be an optimal approach to social and behavior change communication with marginalized communities across multiple social development themes. They indicated the increasing popularity of mobile and other digital media among marginalized communities, especially youth, and the potential for utilizing local communication methods along with new digital media. This hypothesis is supported by findings from one of the field studies, a digital training and communication tools/materials pilot for frontline workers, to improve nutrition behaviors among marginalized communities. They also provided field evidence for the efficacy of mobile technology in civic participation, education, and health. These findings have far‐reaching import for designing inclusive social and behavior change communication programs for marginalized communities where local and mainstream channels (particularly digital) complement each other.